2020
DOI: 10.1007/s00253-020-10822-6
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression concerning fatty acid and amino acid metabolism in Chlorella vulgaris cultured with antibiotics

Abstract: The green alga Chlorella vulgaris has potential as a source of clean bioenergy with abundant metabolites and a high oil content, and antibiotics are often applied to remove bacteria from culture to obtain axenic algal strains. In this work, ceftazidime and gentamicin sulphate (GS) were added separately and in combination in the aseptic processing of C. vulgaris, and gene expression and metabolites were evaluated. The results showed that ceftazidime and GS effectively inhibited the proliferation of Cyanobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…The amino acid content of C. pyrenoidosa was 189.7 mg g −1 , which was consistent with the content of C. pyrenoidosa (186.6 mg g −1 ) in the study of Zhong et al ( 23 ). However, the amino acid content of microalgae depended on different culture conditions, such as medium composition ( 24 26 ), temperature ( 27 ), stress stimulation ( 23 , 28 , 29 ) and other factors ( 30 ). For example, Zhong et al ( 23 ) found that adding 20–80 mg L −1 selenium (Se) could promote amino acid accumulation in C. pyrenoidosa biomass, and the addition of 40 mg L −1 Se achieved the highest amino acid accumulation (237.1 mg g −1 ) among the treatments.…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid content of C. pyrenoidosa was 189.7 mg g −1 , which was consistent with the content of C. pyrenoidosa (186.6 mg g −1 ) in the study of Zhong et al ( 23 ). However, the amino acid content of microalgae depended on different culture conditions, such as medium composition ( 24 26 ), temperature ( 27 ), stress stimulation ( 23 , 28 , 29 ) and other factors ( 30 ). For example, Zhong et al ( 23 ) found that adding 20–80 mg L −1 selenium (Se) could promote amino acid accumulation in C. pyrenoidosa biomass, and the addition of 40 mg L −1 Se achieved the highest amino acid accumulation (237.1 mg g −1 ) among the treatments.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of antibiotics to a culture of algae is a convenient method for controlling bacteria. However, the effects of antibiotics on algae have frequently been reported (Guo et al 2016;Wang and Sheng 2020). Antibiotics can present a serious environmental risk to the environment.…”
Section: Introductionmentioning
confidence: 99%